2012
DOI: 10.1074/jbc.m112.393462
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase of Regenerating Liver 2 (PRL2) Is Essential for Placental Development by Down-regulating PTEN (Phosphatase and Tensin Homologue Deleted on Chromosome 10) and Activating Akt Protein

Abstract: Background:The physiological functions of the PRL phosphatases are poorly understood. Results: PRL2 deficiency causes placental insufficiency, decreased spongiotrophoblast proliferation, and growth retardation. Conclusion: PRL2 plays an important role in placental development by down-regulating PTEN and activating Akt. Significance: This study provides the first evidence of an essential function for PRL2 and offers a biochemical basis for PRLs as oncoproteins to repress PTEN expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
57
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 35 publications
7
57
0
Order By: Relevance
“…Decreased cell proliferation in PRL2 Ϫ/Ϫ placenta appears to be caused by Akt inactivation as a result of up-regulation of the tumor suppressor PTEN. These results provide the first evidence that PRL2 is required for extra-embryonic development by promoting cell proliferation via the PI3K-Akt signaling pathway (31).…”
mentioning
confidence: 60%
See 4 more Smart Citations
“…Decreased cell proliferation in PRL2 Ϫ/Ϫ placenta appears to be caused by Akt inactivation as a result of up-regulation of the tumor suppressor PTEN. These results provide the first evidence that PRL2 is required for extra-embryonic development by promoting cell proliferation via the PI3K-Akt signaling pathway (31).…”
mentioning
confidence: 60%
“…7, C and D). We previously reported that in placenta, PRL2 deficiency led to elevated PTEN expression, an antagonist of PI3K signaling pathway, and therefore decreased Akt activation (31). To examine whether this is also the case in testis, we measured PTEN protein level in germ cells isolated from wild-type and PRL2 Ϫ/Ϫ testes.…”
Section: Prl2 Deficiency Promotes Apoptosis In Germ Cellsmentioning
confidence: 99%
See 3 more Smart Citations